Configuration‐Dependent Photoinduced Electron Transfer in Diastereomeric Naphthalene‐Amino‐Naphthalene Triads. Issue 37 (23rd July 2015) - Nuin, Edurne; Sastre, German; Pischel, Uwe; Andreu, Inmaculada; Miranda, Miguel A.
Abstract Novel diastereomeric triads containing two naphthalene chromophores have been designed in which an electron‐donating amine moiety is covalently integrated into the connecting bridge. Photophysical studies (steady‐state and time‐resolved fluorescence) in solvents of different polarity have been performed. A remarkable stereodifferentiation in the intramolecular fluorescence quenching was found in acetonitrile. Laser flash photolysis gave rise to naphthalene‐derived radical cations, which were also quenched by the amine with an even higher degree of stereodifferentiation. The results are in agreement with thermodynamic estimations and indicate that photoinduced electron transfer (PET) is the main quenching pathway. Furthermore, theoretical calculations have allowed us to explain the experimentally observed stereodifferentiation in PET quenching.